METODE PELAKSANAAN PEKERJAAN RAMP FLY OVER JOMBOR YOGYAKARTA - , EKA MARIS CAHYA PUTRA, Wiryanta, ST., MT. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Because at the intersection of Jombor frequent congestion due to the large volume of vehicles that will go to the city of Yogyakarta or out of town, it will be built to fly over who will have a role in supporting the smooth movement of the traffic flow that will pass through Yogyakarta. To be able to know the process of flyover ramp from the work of determining the coordinates of the point of the ramp up to the spreading asphalt. In the conduct of manufacturing ramp needed some equipment such as Theodolites, Waterpass, Signs Measure, Schafolding, Concrete Pump, Truck Mixer, Excavator, Motor Grader, etc. In the method of making the implementation of flyover ramp Jombor can be summarized as follows : 1) Equally, there are 6 pieces of steel cable tendons and 22 pretegang every tendon in his right side and the left box girder. 2) Stressing process performed after the age of the concrete reaches 100%.